The Influence Of Inflation, Rupiah Exchange Rate, International Wheat Price, and Import Price On Wheat Imports From Australia In 2010-2023 - Catherina Natalia Adinda Widyaputri; Ni Ketut Budiningsih (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Indonesia, as a country with an open economic system, engages in international trade to meet domestic needs. Wheat is one of the commodities imported due to high domestic demand and the limitations of a tropical climate that hinder local wheat cultivation. Consequently, Indonesia has continued importing wheat from the New Order era to the present. It is said that Indonesia has become dependent on wheat imports. One of the main wheat suppliers to Indonesia is Australia, with import volumes showing a fluctuating trend from 2010 to 2023. These fluctuations are affected by several factors, including inflation, the Rupiah exchange rate, worldwide wheat prices, and import expenses. This study seeks to: (1) Evaluate the concurrent effects of inflation, the Rupiah currency rate, world wheat prices, import costs in respect to Australia's wheat imports volume; (2) examine the individual effects of inflation, the Rupiah exchange rate, international wheat prices, and import prices Regarding the wheat import volume from Australia; and (3) explore the short-term and long-term impacts of each variable. Using monthly time series data from January 2010 to December 2023, this study employs a quantitative approach under Error Correction Model (ECM). The study's results demonstrate that inflation, the Rupiah exchange rate, international wheat prices, and import prices collectively exert a considerable influence Regarding the wheat import volume from Australia. Inflation and worldwide wheat prices exert a considerable positive impact, whilst import costs and the Rupiah exchange rate impose a major negative effect. Over the long term, all variables substantially influence wheat import volumes; conversely, in the near term, only import prices exert a negative and significant effect.